Implementation, Withholding, and Reporting Analysis of Income Tax Article 26 Based on a Tax Treaty - Arif Darmawan; Intan Wulandari (Journal of Applied Accounting and Taxation, 2016)
The purpose of this research is to know how to use the application procedures for cash receipts finance and billing management system (FBMS). This research was conducted in the Office of Sea port of Batam engaged in the field of port services in Batam. The method used in this research is descriptive analysis method. The results of this study can be concluded that the procedures for cash receipts to the Office of the Port of Batam is in conformity with the existing theory, but an oversight in the use of the application system of cash receipts should be noted that the report produced more accurate. Suggestions to the authors convey to always pay attention to input data with care and to improve FBMS to avoid mistakes.